Delayed bilateral spontaneous renal rupture after surgery for unilateral upper ureteral calculi: a case report - Tang, Wen; Yang, Denghao; Wu, Tao; Liang, Guobiao (Frontiers in Medicine, 2023)
Spontaneous renal rupture is a rare clinical condition characterized by spontaneous bleeding in the renal subcapsular and perinephric spaces in patients without a history of trauma. It occurs mainly in pathologic kidneys and after some renal surgeries. We report a 40-year-old male patient admitted with a diagnosis of gallstones with cholecystitis due to fever and abdominal pain after unilateral ureteral calculi. The patient developed delayed right renal rupture hemorrhage during treatment, controlled after selective arterial embolization (SAE). Still, the patient developed spontaneous left renal rupture due to a systemic inflammatory response. Finally, the patient’s life was saved after several selective embolizations of the renal artery. We retrospectively analyzed this case to improve our understanding of the disease.